Recent advances in the microbial production of C4 alcohols by metabolically engineered microorganisms. Issue 3 (28th May 2021) - Yoo, Jee In; Sohn, Yu Jung; Son, Jina; Jo, Seo Young; Pyo, Jiwon; Park, Su Kyeong; Choi, Jong‐Il; Joo, Jeong Chan; Kim, Hee Taek; Park, Si Jae
Abstract: Background: The heavy global dependence on petroleum‐based industries has led to serious environmental problems, including climate change and global warming. As a result, there have been calls for a paradigm shift towards the use of biorefineries, which employ natural and engineered microorganisms that can utilize various carbon sources from renewable resources as host strains for the carbon‐neutral production of target products. Purpose and Scope: C4 alcohols are versatile chemicals that can be used directly as biofuels and bulk chemicals and in the production of value‐added materials such as plastics, cosmetics, and pharmaceuticals. C4 alcohols can be effectively produced by microorganisms using DCEO biotechnology (tools to design, construct, evaluate, and optimize) and metabolic engineering strategies. Summary of New Synthesis and Conclusions: In this review, we summarize the production strategies and various synthetic tools available for the production of C4 alcohols and discuss the potential development of microbial cell factories, including the optimization of fermentation processes, that offer cost competitiveness and potential industrial commercialization. Graphical Abstract and Lay Summary: C4 alcohols are versatile chemicals that can be used directly as biofuels and bulk chemicals and in the production of value‐added materials such as plastics, cosmetics, and pharmaceuticals. In this review, we summarize the production strategies and various synthetic tools available for the production of C4 alcohols and discuss the potential development of microbial cell factories, including the optimization of fermentation processes that offer cost competitiveness and potential industrial commercialization.